Place Dependence in the Coffee Truck Area: A Case Study on Jalan Teuku Hamzah Bendahara, Lhokseumawe City - Wahyu Aulia; Cut Azmah Fithri; Hendra Aiyub; Yenny Novianti (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The phenomenon of coffee trucks has rapidly developed in various cities across Indonesia, including on Jalan Teuku Hamzah Bendahara in Lhokseumawe City. This area utilizes pedestrian pathways as a dynamic public interaction space, attracting numerous visitors to engage in activities and fulfill their social and consumption needs. This study aims to measure the level of place dependence and examine the relationships between various variables such as perceived quality, need fulfillment, loyalty, effort to stay, and effort to return in the coffee truck area. The methodology employed is a quantitative survey using questionnaires completed by 100 respondents, with data analyzed using SPSS. The findings show that the level of place dependency is quite high, indicating a strong attachment to this location. User satisfaction regarding the quality of the space provided by the coffee truck shows a strong and significant relationship, contributing notably to enhancing the perception of this location as the best in meeting visitors' needs and goals overall. In conclusion, the coffee truck area not only fulfills users' functional needs but also fosters emotional connections, thereby strengthening their dependence on the location. The results of this study offer valuable insights for managing similar public spaces, particularly in creating places that can establish long-term engagement with users and communities.